A Market In Vogue, Fashion Photography in Sweden - АсперсПатрик Асперс (Journal of Economic Sociology, 2010)
The current research is aimed at understanding and explaning of so called markets of esthetical goods. We take picture fashion in Sweden as an example. In order to understand and explain a market from the sociological point of view we need to disclose the way how the senses are constructed on this concrete market. The actors construct the esthetical values on this market. On the basis of the relations between the producers and consumers the status identities are formatted. Camera operators chose their own author styles and the combination of status and style end up in market identity. The distribution of styles structures the prices. The conclusion of the paper is that the markets of esthetical goods could be defined as mechanisms of status identity creation. This also suggests that this approach towards markets of esthetical goods could be useful for study the other markets as well.